Risks of Increased Defensive Medicine Due to the Medical World Digitalization and the Legal Implications Based on Indonesian Health Laws - Ginting, James Davidta; Yanto, Oksidelfa; Suminar, Sri Ratna (Sinergi International Journal of Law, 2026)
Digitalization in the healthcare sector, such as electronic medical records (EMR), has opened new horizons in the storage and management of patient medical records. This may also trigger an increase in defensive medicine practice, namely providing more careful medical treatment just to avoid potential lawsuits even though it is not always mesdically necessary. This research aims to study the risk of increased defensive medicine from the digitalization of medical records and the legal implications that arise and evaluate the extent to which legal regulations in Law Number 17 of the Year 2023 concerning Health in addressing defensive medicine practices. The method used is juridical analysis using a literature study approach that examines various legal literature, statutory regulations, and previous research related to digitalization in the medical world and the legal responsibilities of medical personnel. According to the results of this research, it was found that although digitalization can increase the efficiency of health services, it also risks exacerbating the practice of defensive medicine in Indonesia. Existing legal regulations are not yet responsive enough to overcome this challenge, especially in balancing the protection of the rights of both patients and medical personnel.